2020
DOI: 10.3389/fmicb.2020.02043
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Fermentation Broth of Bacillus velezensis Strain S3-1 Improves Pak Choi Nutritional Quality and Changes the Bacterial Community Structure of the Rhizosphere Soil

Abstract: Bacillus velezensis is a plant growth-promoting rhizobacteria (PGPR) that has long been proven to improve the growth of plants, and it has been widely used in agriculture. However, in many reports, we observed that during the application of bacterial fluids, it appeared that the effect of the cell-free fermentation broth (CFB) was ignored. The purpose of this study is to compare the effect of the no inoculation treatment (CK), the B. velezensis strain S3-1 treatment (S), the CFB treatment in the Pak choi, soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Increased soil P and K availability, according to published research, is directly linked to lower soil pH. Plant roots can absorb P and K to release OH − , which neutralizes H + in the soil and stabilizes the pH [ 46 , 47 ]. We believe that active microbial acid secretion and steady plant P and K uptake are responsible for the build-up of P and K in the inoculated soil.…”
Section: Discussionmentioning
confidence: 99%
“…Increased soil P and K availability, according to published research, is directly linked to lower soil pH. Plant roots can absorb P and K to release OH − , which neutralizes H + in the soil and stabilizes the pH [ 46 , 47 ]. We believe that active microbial acid secretion and steady plant P and K uptake are responsible for the build-up of P and K in the inoculated soil.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the co-inoculation of B. velezensis S141 with Bradyrhizobium diazoefficiens USDA110 into soybean resulted in enhanced nodulation and nitrogen fixation efficiency by producing larger nodules [ 48 ]. In another related study, the members of OG Ba were able to solubilize phosphate, and produce IAA, ACC deaminase and siderophores [ 49 , 50 , 51 ].…”
Section: The Importance and Applications Of The Og Bamentioning
confidence: 99%
“…Several waste products have been proven to be suitable for industrial inoculant production [99,90]; using waste products can lower production costs, which are a main limiting factor in the commercialization of bio-inocula, thus making their use attractive to manufacturers. Moreover, the production of cell-free fermentation liquids with strong phyto-stimulating and biocontrol properties [6,91] should increase manufacturers' interest due to the independence from interactions with the soil micro-and macro-biota. A specific production method is required for AMF-based products: the obligate biotrophic nature of AMF has, indeed, complicated the development of cost-efficient large-scale production methods to obtain high-quality AMF inoculum [92].…”
Section: Fermentation and Formulation Of Bioinoculantsmentioning
confidence: 99%